2021
DOI: 10.1002/ptr.7179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcuminoids on inflammatory and oxidative stress biomarkers and clinical outcomes in critically ill patients: A randomized double‐blind placebo‐controlled trial

Abstract: Experimental studies have suggested the beneficial effects of curcuminoids as natural polyphenols against traumatic brain injury (TBI). The aim of this study was to investigate the effects of supplementation with curcuminoids on inflammatory and oxidative stress biomarkers, clinical outcomes and nutritional status in critically ill patients with TBI. A total of 62 ICU‐admitted adult patients with TBI were randomly allocated to receive either a daily dose of 500 mg curcuminoids or matched placebo via enteral nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Generally, curcumin is a safe phytochemical and well‐tolerated. This food supplement has been used in different diseases even in critical health conditions such as cancer patients and trauma and sepsis patients in the intensive care unit without any considerable adverse effects (Aggarwal, Kumar, & Bharti, 2003; Dhillon et al, 2008; Hsieh, 2001; Karimi et al, 2020; Zahedi et al, 2021). It is shown that supplementation with 8,000 mg curcumin/day for 3 months resulted in no toxicity, only some gastrointestinal discomfort, namely, nausea and diarrhea (Chainani‐Wu, 2003; Hsu & Cheng, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, curcumin is a safe phytochemical and well‐tolerated. This food supplement has been used in different diseases even in critical health conditions such as cancer patients and trauma and sepsis patients in the intensive care unit without any considerable adverse effects (Aggarwal, Kumar, & Bharti, 2003; Dhillon et al, 2008; Hsieh, 2001; Karimi et al, 2020; Zahedi et al, 2021). It is shown that supplementation with 8,000 mg curcumin/day for 3 months resulted in no toxicity, only some gastrointestinal discomfort, namely, nausea and diarrhea (Chainani‐Wu, 2003; Hsu & Cheng, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The required sample size in each group has been equal to 24 people, and with considering the drop out patients, the sample size will be practically 30 patients in every group, which we will consider a total of 60. It seems that this sample size is small; however, several articles which conducted among ICU patients used a small sample size based on a formula like our ones and worked on about 60 patients [ 26 28 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…Of the studies investigating TBI-related curcumin between 2005 and 2022, 42 were clinical trials. 30,31 The number of studies investigating curcumin in TBI through drug delivery system is three [32][33][34] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant decrease in serum leptin levels in the curcuminoids group compared to the placebo group; however, despite supplementation with curcuminoids, serum concentrations of adiponectin in cases with TBI did not change. 30 Zahedi et al 31 reported that the effects of curcuminoid supplementation on inflammatory and oxidative stress biomarkers, clinical outcomes, and nutritional status in critically ill patients with TBI are unknown, although the beneficial effects of polyphenolic curcuminoids in the treatment of TBI have been proposed in experimental studies. In one such study, serum levels of interleukin-6, tumor necrosis factor-alpha, monocyte chemoattractant protein-1, and C-reactive protein were significantly decreased in patients treated with curcuminoid compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%